Parental Emotion Regulation and Parenting Stress in Early Childhood: The Moderating Role of Social Support - Kotrun Nada Kusesi; Ika Ariyati; Agus Setiawan (Suluh: Jurnal Bimbingan dan Konseling, 2026)
Background: Early childhood parenting represents a crucial phase in family development that requires a high level of emotional involvement from parents. During this period, parents face various parenting demands related to meeting children’s physical needs as well as supporting their emotional and social development. Such conditions may increase the risk of parenting stress, particularly when parents experience difficulties regulating their emotions or lack adequate support from their social environment. Aim: Therefore, this study aims to analyze the effect of emotion regulation on parenting stress among parents of young children and to examine the moderating role of social support in this relationship. Method: This study employed a quantitative approach using a survey parents of students at RA Muslimat NU 07 as research participants. Data were collected using three standardized psychological instruments: the Emotion Regulation Questionnaire (ERQ) to measure parents’ emotion regulation, the Parental Burnout Assessment (PBA) to assess the level of parenting stress, and the Multidimensional Scale of Perceived Social Support (MSPSS) to measure perceived social support. Data analysis was conducted using simple regression to examine the direct effects of emotion regulation and social support on parenting stress. Result and Disscussions: The results indicate that emotion regulation and social support do not have a significant simultaneous effect on parenting stress (F = 0.357; p = 0.701; R² = 0.011). Partially, emotion regulation (p = 0.866) and social support (p = 0.486) also do not show a significant effect on parenting stress. Furthermore, the moderation test reveals that the interaction between emotion regulation and social support is not significant (p = 0.387), indicating that social support does not function as a moderating variable in this relationship. Conclusion: These findings suggest that emotion regulation and social support are not the main determinants of parenting stress among parents of young children in this study, indicating that other factors may play a more dominant role in influencing parenting stress beyond the variables examined.